Electronic monitoring devices in asthma: translating from study use into clinical practice - Adejumo, Ireti D. (2021)
Introduction Asthma is increasingly recognised to be a heterogeneous disease with outcomes mediated by psychosocial and behavioural factors as well as by pathophysiological mechanisms. Inhaled corticosteroids (ICS) have long been the mainstay of treatment for asthma and poor ICS adherence has been shown to be associated with adverse outcomes. Despite this, poor ICS adherence has remained a persistent challenge for clinicians and patients with difficulties in both its measurement and management.